Students Perception on the use of Project-Based Learning in Software Engineering Education - Souza, Maurício; Moreira, Renata Teles; Figueiredo, Eduardo (Anais Estendidos do Simpósio Brasileiro de Engenharia de Software (SBES); 2019: Anais Estendidos do XXXIII Simpósio Brasileiro de Engenharia de Software, 2020)
Balancing theory and practice is a recurring challenge in Software Engineering (SE) education. However, the curriculum guidelines of the ACM/IEEE and Brazilian Computer Society emphasize the need of providing students with sufficient practical experiences for the development of competences expected for SE professional. Student-centered and learn-by-doing approaches, such as Project-Based Learning (PBL), have been advocated as suited for the development of competences. These approaches aim to promote higher motivation for the learner, a more active role in the learning process, and better learning in the application level. The goal of this paper is to evaluate the students' perception on the adoption of PBL in SE education. To achieve this goal, we performed a long-term study spanning for about 2 years. This study includes a survey to collect responses of 32 undergraduate students enrolled in an introductory SE course that used PBL. We compare the results to the responses of 17 students who participated in a SE course with similar syllabus but with a traditional teacher-centered learning method (non-PBL). Our results show a positive reception of the PBL method, and an increased perception of the contribution of a practical software development assignment in learning specific SE topics in the context of the PBL course, in comparison to a non-PBL method.